2021
DOI: 10.2147/cmar.s316428
|View full text |Cite
|
Sign up to set email alerts
|

MRPL13 Act as a Novel Therapeutic Target and Could Promote Cell Proliferation in Non-Small Cell Lung Cancer

Abstract: Background:The latent involvement of MRPL13 in non-small cell lung cancer (NSCLC) remains unclear. This study aimed to explore the role of MRPL13 in NSCLC. Methods: All analyses were performed in R software 4.0, SPSS version 23, and GraphPad Prism 8. The "limma" package was used to identify differentially expressed genes. Univariate and multivariate cox analyses were used to identify prognosis-related genes. A549 and H1299 lung cancer cell lines were selected for phenotypic experiments.Results: The high level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Bioinformatic data analyses combined with in vitro and in vivo experimental results have revealed that MRPL13 is highly expressed in non-small cell lung cancer tissues and cell lines and can promote cancer cell proliferation; the locus is, therefore, an independent tumor marker and candidate therapeutic target (51). Expression levels of MRPS6, MRPS10, MRPS23, and MRPS31 are significantly elevated in breast cancer cells and tissues, and these findings have been corroborated by corresponding cell-based functional assay results (52,53).…”
Section: Differential Gene Expressionmentioning
confidence: 99%
“…Bioinformatic data analyses combined with in vitro and in vivo experimental results have revealed that MRPL13 is highly expressed in non-small cell lung cancer tissues and cell lines and can promote cancer cell proliferation; the locus is, therefore, an independent tumor marker and candidate therapeutic target (51). Expression levels of MRPS6, MRPS10, MRPS23, and MRPS31 are significantly elevated in breast cancer cells and tissues, and these findings have been corroborated by corresponding cell-based functional assay results (52,53).…”
Section: Differential Gene Expressionmentioning
confidence: 99%
“…Linlin Liu et al 12 reported that the bioinformatics results provide evidence of the potential of mitochondrial ribosomal genes as cancer biomarkers. Annamaria Gal et al 13 and Wei Zhang et al 14 reported the strong correlation between mitochondrial translation genes and NSCLC prognosis. Wang et al 15 revealed that MRPS16 enhances tumour cell growth by PI3K/AKT signal path, demonstrating the critical role played by MRPS16 in biological processes further.…”
Section: Introductionmentioning
confidence: 99%
“…By modulating mitochondrial translation, this dysregulation changes tumor metabolism and increases tumor heterogeneity, invasion, treatment resistance, and metastasis [ 31 , 42 ]. The high expression of MRPL15 and MRPL38 indicates poor prognosis in non-small cell lung cancer and ovarian cancer [ 43 , 44 ]. The expression of MRPL13 in breast cancer is significantly higher than that in normal tissues, and it can promote tumor cell proliferation and migration through the PI3K/Akt/mTOR signaling pathway [ 45 ].…”
Section: Introductionmentioning
confidence: 99%